International spillovers, productivity growth and openness in Thailand: an intertemporal general equilibrium analysis - Diao, Xinshen; Rattso, Jorn; Stokke, Hildegunn Ekroll (International Food Policy Research Institute, 2002)
Thailand has experienced economic growth well above world averages for about 40 years. It is a challenge to understand the sources of this high growth path, and in particular why growth has not slowed down with assumed decreasing returns to capital. We develop an intertemporal general equilbrium model separating between agriculture and industry, and with open capital market and endogenous productivity growth to analyze the underlying adjustment mechanisms. Foreign technology spillover embodied in trade is assumed to be the driving force of the productivity growth, consistent with econometric evidence. The high growth experience is understood as a transition path with interaction between productivity growth, openness and capital investment. Counterfactual analysis shows how protection may have had serious detrimental effect on growth rate due to productivity and investment slowdown. The role of relative prices in constraining growth is investigated, inspired by the Acemoglu-Ventura hypothesis of growth slowdown due to terms of trade effect. In our setting, low elasticity between domestic and exports goods in supply leads to large relative price shifts for domestic goods, but promotes investment and growth during transition.